2014
DOI: 10.1080/09291016.2014.884304
|View full text |Cite
|
Sign up to set email alerts
|

Strength-training and biological rhythm of male sex hormone among judoists

Abstract: Testosterone is a steroid hormone that is secreted by the testes with a diurnal rhythm and has a strong anti-catabolic (anabolic) effect on muscles. There is a strong relationship (r > 0.9) between concentrations of testosterone in the saliva and blood. The main purpose of the current study is to investigate the effect of strength-training on levels of salivary testosterone in male judoists. In a cross-sectional investigation, a population of 18 fit young male judoists (aged 17.0 ± 1.2 year, body mass 72 ± 3 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…In an attempt to determine and compare the effects of different types of resistance training on the circadian rhythm of endocrine hormones, a cross-sectional study was employed on Judoists [6]. This study confirmed previous findings when it found that resistance training, irrespective of the type, failed to alter the circadian rhythm of hormone concentrations.…”
supporting
confidence: 70%
“…In an attempt to determine and compare the effects of different types of resistance training on the circadian rhythm of endocrine hormones, a cross-sectional study was employed on Judoists [6]. This study confirmed previous findings when it found that resistance training, irrespective of the type, failed to alter the circadian rhythm of hormone concentrations.…”
supporting
confidence: 70%
“…A host of scientists have discovered that the beat domains of physically healthy or physically energetic persons are higher than those possessed by out-of-form or inactive subjects [4,44,45], However, these suggestive contacts are highly confounding and complex. The fact that a rhythm domain of this vast a magnitude could be infl uenced by the physiological version within a more superior context, or "synchronised" by a consistent physical activity and thus inciting a more pronounce experiential rhythm, remains uncertain [46]. Nevertheless, a silver lining exists; such a gap may provide a new research topic for future scholars.…”
Section: Discussionmentioning
confidence: 99%
“…Se eligió colectar muestras de saliva, por su naturaleza no invasiva, lo que no genera estrés en los niños, favoreciendo a la obtención de la autorización parental y cooperación del niño; además de ser fácil de obtener, y porque no necesita especial entrenamiento para el evaluador (Shariat, Kargarfard, Tamrin, Danaee & Karimi, 2014). Otra razón es la independencia de la tasa de flujo, ya que el cortisol salival representa la fracción biológicamente activa y libre de cortisol en sangre en respuesta al ejercicio (Gozansky, Lynn, Laudenslager & Kohrt, 2005;Papacosta & Nassis, 2011); y es una técnica de las más usadas actualmente (Silva, Mallozi & Ferrari, 2007).…”
Section: Procedimientounclassified